Safety leadership at construction sites: the importance of rule-oriented and participative leadership - Martin Grill; Anders Pousette; Karina Nielsen; Regine Grytnes; Marianne Törner (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The construction industry accounted for >20% of all fatal occupational accidents in Europe in 2014. Leadership is an essential antecedent to occupational safety. The aim of the present study was to assess the influence of transformational, active transactional, rule-oriented, participative, and laissez-faire leadership on safety climate, safety behavior, and accidents in the Swedish and Danish construction industry. Sweden and Denmark are similar countries but have a large difference in occupational accidents rates. METHODS: A questionnaire study was conducted among a random sample of construction workers in both countries: 811 construction workers from 85 sites responded, resulting in site and individual response rates of 73% and 64%, respectively. RESULTS: The results indicated that transformational, active transactional, rule-oriented and participative leadership predict positive safety outcomes, and laissez-faire leadership predict negative safety outcomes. For example, rule-oriented leadership predicts a superior safety climate (β=0.40, P<0.001), enhanced safety behavior (β=0.15, P<0.001), and fewer accidents [odds ratio (OR) 0.78, 95% confidence interval (95% CI) 0.62-0.98]. The effect of rule-oriented leadership on workers' safety behavior was moderated by the level of participative leadership (β=0.10, P<0.001), suggesting that when rules and plans are established in a collaborative manner, workers' motivation to comply with safety regulations and participate in proactive safety activities is elevated. The influence of leadership behaviors on safety outcomes were largely similar in Sweden and Denmark. Rule-oriented and participative leadership were more common in the Swedish than Danish construction industry, which may partly explain the difference in occupational accident rates. CONCLUSIONS: Applying less laissez-faire leadership and more transformational, active transactional, participative and rule-oriented leadership appears to be an effective way for construction site managers to improve occupational safety in the industry.